2017
DOI: 10.1109/tim.2017.2753384
|View full text |Cite
|
Sign up to set email alerts
|

Robust Microwave Characterization of Inkjet-Printed Coplanar Waveguides on Flexible Substrates

Abstract: Abstract-In this paper, we propose a robust microwave characterization of inkjet printed components on flexible substrates, which aim at measuring the material properties of silver nanoparticle inks and the supporting dielectric spacer employed during measurements. Starting with propagation constant extracted from multiline thru-reflect-line calibration with coplanar waveguide (CPW) standards and then proceeding with finite element modeling of CPWs, the proposed technique can dynamically produce an interpolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…One of the representative methods is sintering, which improves conductivity by removing binders and organic stabilizers and forming connections between nanoparticles, and controlling its temperature. For instance, when the sintering temperature of a pattern based on silver nanoparticles was 220 • C, the conductivity was 0.206 × 10 7 S/m, which was higher than 0.192 × 10 7 S/m at 170 • C [137]. High sintering temperatures increase the bond strength between particles and grow the crystalline structure, providing an efficient path for electrons to move freely.…”
Section: Metal Nanoparticlesmentioning
confidence: 98%
“…One of the representative methods is sintering, which improves conductivity by removing binders and organic stabilizers and forming connections between nanoparticles, and controlling its temperature. For instance, when the sintering temperature of a pattern based on silver nanoparticles was 220 • C, the conductivity was 0.206 × 10 7 S/m, which was higher than 0.192 × 10 7 S/m at 170 • C [137]. High sintering temperatures increase the bond strength between particles and grow the crystalline structure, providing an efficient path for electrons to move freely.…”
Section: Metal Nanoparticlesmentioning
confidence: 98%
“…The plots for measured dielectric constant and loss tangent as a function of frequency as reported in Reference are shown in Figure . A robust microwave characterization algorithm for extracting dielectric properties as well as ink conductivity was proposed in Reference . The advantage of this approach lies in the automation of all the sub‐tasks involved in modeling and optimization, facilitating an efficient parameter extraction framework.…”
Section: Recent Progress In Substrate Technologiesmentioning
confidence: 99%
“…It was observed that losses decrease by about (40 dB/m) at 20 GHz when the sintering temperature was changed from 170°C to 220°C. Furthermore, the characteristic impedance for the inkjet printed CPWs on Kapton was extracted . In Reference , Kim et al proposed thick and thin film processes on fabric, and their electrical characteristics were evaluated to investigate the performance and limits of the screen printing circuit technology.…”
Section: Recent Progress In Substrate Technologiesmentioning
confidence: 99%
“…One such technique which can help the advancements towards this common goal is known as 3D printing, and it is already being employed to produce parts for industries such as automotive with greater speed and accuracy. To facilitate the process of 3D printing for sensor manufacturing, ink-jet printing, a technology commonly used in both personal and commercial environments, has surfaced in preference to conventional electronics fabrication practices [11][12][13][14]. Au et al compared the cost of a traditionally manufactured sensor, i.e., via lithography, to a 3D printed technology, i.e., stereolithography and found the difference to be 15 USD [15].…”
Section: Introductionmentioning
confidence: 99%